Rare Presentations of Male Breast Cancer: A Case Series Highlighting Diagnostic and Therapeutic Challenges - Chandra Budi Hartono; Widyanti Soewoto (HM Publisher, 2025)
Male breast cancer (MBC) is a rare disease with a rising incidence, accounting for less than 1% of all breast cancer cases. It typically presents in older men and outcome-based studies in adolescent and young adult (AYA) males are scarce due to its rarity. This case series aims to highlight the diagnostic and therapeutic challenges encountered in two rare presentations of MBC. The first case involved an 18-year-old male who presented with left chest pain and a rapidly growing breast mass. Histopathological analysis revealed invasive ductal carcinoma (IDC) NST grade III with positive margins, staged as cT2N0M0. He also presented with anemia and elevated transaminase enzymes. The second case was a 59-year-old male with a history of mucinous adenocarcinoma of the right breast who presented with the right arm and shoulder pain and a supraclavicular mass. Imaging revealed extensive metastatic disease in the lungs, liver, and bones, and he was diagnosed with cT2N3cM1. Both patients underwent different treatment approaches based on their disease stage and presentation. In conclusion, MBC, especially in AYA patients, presents unique diagnostic and therapeutic challenges due to its rarity and potential for aggressive behavior. These cases underscore the importance of considering MBC in differential diagnoses, even in younger males, and the need for tailored treatment strategies based on the specific clinicopathological features and stage of the disease. Early detection, comprehensive nodal evaluation, and adherence to established treatment guidelines are crucial for improving outcomes in MBC patients. Further research is warranted to better understand the biological characteristics and optimal management of MBC in rare presentations and younger populations.